A Revised Structure Model for the UCl6 Structure Type, Novel Modifications of UCl6 and UBr5, and a Comment on the Modifications of Protactinium Pentabromides. Issue 25 (8th April 2019) - Deubner, H. Lars; Rudel, Stefan S.; Sachs, Malte; Pietzonka, Clemens; Karttunen, Antti J.; Ivlev, Sergei I.; Müller, Matthias; Conrad, Matthias; Müller, Ulrich; Kraus, Florian
Abstract: The redetermination of the crystal structure of trigonal UCl6, which is the eponym for the UCl6 structure type, showed that certain atomic coordinates had been incorrectly reported. This led to noticeably different U−Cl distances within the octahedral UCl6 molecule (2.41 and 2.51 Å). Within the revised structure model presented here, which is based on single crystal data as well as quantum chemical calculations, all U−Cl distances are essentially equal within standard uncertainty (2.431(5), 2.437(5), and 2.439(6) Å). This room temperature modification, called rt‐UCl6, crystallizes in the trigonal space group P 3 ‾ m 1, No. 164, hP 21, with a= 10.907(2), c= 5.9883(12) Å, V= 616.9(2) Å 3, Z= 3 at T= 253 K. A new low‐temperature (lt) modification of UCl6 is also presented that was obtained by cooling a single crystal of rt‐UCl6. The phase change occurs between 150 and 175 K. lt‐UCl6 crystallizes isotypic to a low‐temperature modification of SF6 in the monoclinic crystal system, space group C 2/ m, No. 12, mS 42, with a= 17.847(4), b= 10.8347(18), c= 6.2670(17) Å, β =96.68(2)°, V= 1203.6(5) Å 3, Z= 6 at 100 K. The Cl anions form a close‐packed structure corresponding to the α‐Sm type with uranium atoms in the octahedral voids. During the synthesis of UBr5 a new modification was obtained that crystallizes in the triclinic crystal system, space group P 1 ‾, No. 2, aP 36, with a= 10.4021(6), b= 11.1620(6), c= 12.2942(7) Å, α =68.3340(10)°, β =69.6410(10)° and γ =89.5290(10)°, V= 1231.84(12) Å 3, Z= 3 at T= 100 K. In this structure the UBr5 units are dimerized to U2 Br10 molecules. The Br anions also form a close‐packed structure of the α‐Sm type with adjacent uranium atoms in the octahedral voids. Comparisons of the crystal structures of the compounds MX 5 ( M =Pa, U; X =Cl, Br) show that the crystal structure of monoclinic α‐PaBr5 is probably not correct. Abstract : Crystal clear : A revised structure for UCl6 from single‐crystal diffraction and calculations has essentially equal U−Cl distances. Phase transition leads to a new low‐temperature modification. Additionally a new trigonal modification of UBr5 was also discovered.